2011
DOI: 10.5334/ijic.530
|View full text |Cite
|
Sign up to set email alerts
|

Integrated care in Norway: State of affairs years after regulation by law

Abstract: Introduction: A mandatory multidisciplinary plan for individual care, the 'Individual care Plan', was introduced by law in Norway in 2001. The regulation was established to meet the need for improved efficiency and quality of health and social services, and to increase patient involvement. The plan was intended for patients with long-term and complex needs for coordinated care. The aim of this study was to elaborate on knowledge of such planning processes in Norwegian municipalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
1
34
0
1
Order By: Relevance
“…In 2002, the central Norwegian government took ownership of all public hospitals, creating a highly centralized health care system [53,54]. In 2001, Norway introduced the right of every patient to have an Individual Care Plan, which names a person who coordinates that patient's care across the health care system [55,56]. The focal point in this policy remains strongly with the patient.…”
Section: Individual Patient Level Integration: the Example Of Norwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In 2002, the central Norwegian government took ownership of all public hospitals, creating a highly centralized health care system [53,54]. In 2001, Norway introduced the right of every patient to have an Individual Care Plan, which names a person who coordinates that patient's care across the health care system [55,56]. The focal point in this policy remains strongly with the patient.…”
Section: Individual Patient Level Integration: the Example Of Norwaymentioning
confidence: 99%
“…For one, since there is less structural collaboration between professionals and institutions, it runs the risk of becoming highly dependent on the ability and willingness of case managers to create such a plan. Research from 2011 suggests that only about 17% of eligible patients actually had an individual plan [55], while other research has even questioned the effectiveness of case managers [57]. The Norwegian government has positively evaluated its policies and will thus maintain its course.…”
Section: Individual Patient Level Integration: the Example Of Norwaymentioning
confidence: 99%
“…5,6 Denmark The first time the need for collaboration was commented on in Denmark was in the report by the Coordinating Committee for the National Health Service. 7 The Public Health Insurance Act 8 stipulated that the then county councils and municipalities had to jointly plan their treatment efforts.…”
Section: Norwaymentioning
confidence: 99%
“…The fact that organizational and cultural obstacles are thus able to endure may be one reason for the relatively modest effect of individual plans in practice. 5 Despite the treatment plan, with its patient-related goals and in many cases a coordinator appointed for the treatment, these endeavours are deemed insufficiently powerful to counteract the negative effects of the fragmented range of healthcare services. 6 According to the presented theory, there is no inter-organizational integration, and thus neither are there any opportunities for collaborative synergy.…”
Section: Norwaymentioning
confidence: 99%
“…Studies have shown that the plan improves self‐management, increases patient centredness and reduces unnecessary care use (Burt et al., ; Newbould et al., ). However, several studies (Bjerkan, Richter, Grimsmo, Helles, & Brender, ; Burt et al., ; Jansen et al., ; Newbould et al., ; Reeves et al., ) have shown that the implementation of care planning at primary healthcare clinics is meagre.…”
Section: Introductionmentioning
confidence: 99%